2020
DOI: 10.26434/chemrxiv.11987541.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flooded by Success: On the Role of Electrode Wettability in CO2 Electrolyzers That Generate Liquid Products

Abstract: Economic operation of carbon dioxide (CO2) electrolyzers generating liquid products will likely require high reactant conversions and product concentrations, conditions anticipated to challenge existing gas diffusion electrodes (GDEs). Notably, electrode wettability will increase as lower surface tension products (e.g., formic acid, alcohols) are introduced into electrolyte streams potentially leading to flooding. To understand the hydraulically stable operating envelopes in mixed aqueous-organic liquid domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The production of liquid products is known to induce flooding in the electrolyzer due to the low surface tension of these liquids. 28 Despite not perfectly simulating in situ operation due to the effect of electro-wetting, these ex situ measurements provide an indication of the wettability of the layer and suggest that the adlayer protects the catalyst layer from excessive hydration that would normally dilute the produced ethanol.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The production of liquid products is known to induce flooding in the electrolyzer due to the low surface tension of these liquids. 28 Despite not perfectly simulating in situ operation due to the effect of electro-wetting, these ex situ measurements provide an indication of the wettability of the layer and suggest that the adlayer protects the catalyst layer from excessive hydration that would normally dilute the produced ethanol.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The hydro- phobicity of the GDL is important for the prevention of electrode flooding. 27,28 By analyzing the surface wettability using pure water, 0.1 M KHCO 3 (the anolyte used for performance testing), and 20 wt % ethanol in water solution (a low surface tension alcohol/water mixture), we found that the adlayer significantly changes the surface wettability of the Cu/ PTFE (Figure 4a and Table S3). It is evident from Figure 4a that the ratio of EC to CB has a strong effect on the surface contact angle, with a 1:2 EC/CB ratio having the most hydrophobic surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Several studies suggest that flooding of GDEs is the key way in which electrolytes create CO 2 -depleted zones, leading to the dominance of HER. [60][61][62] Among other operational parameters, pressure has a unique role in CO 2 RR as it has a threefold effect: capillary effects on the electrode flooding, mechanical effects providing better contact between electrolysis cell components, and increase in CO 2 concentration in the gas phase and therefore the CO Ã 2 surface coverage on the catalyst. By means other than manipulating pressure, researchers have controlled CO Ã…”
Section: Doi: 101002/ente202200972mentioning
confidence: 99%
“…As mentioned, catalysts producing more C 2þ relative to C 1 products may be more stable due to a possible graphitic intermediate in the C 1 route. [35,36,47,[59][60][61][62][63] In mechanistic studies conducted by Rahaman et al [43] and Akhade et al, [58] the poisoning C* species is postulated to be formed via reduction of COH*, which is an intermediate of CO*-to-CH 4 reduction. As discussed in the following subsections, abundant CO* coverage provided by back pressure suppresses C 1 hydrocarbon production (CH 4 ) and promotes C 2þ selectivity.…”
Section: Her Suppression Under Back Pressurementioning
confidence: 99%
See 1 more Smart Citation